Capillary-condensation hysteresis in naturally-occurring nanoporous media. (1st March 2020) - Barsotti, Elizabeth; Tan, Sugata P.; Piri, Mohammad; Chen, Jin-Hong
Graphical abstract: Highlights: Capillary condensation isotherms were measured in cores from a shale gas reservoir. Capillary condensation hysteresis was observed at reservoir temperatures. Scanning isotherms were used to provide new insights into the origins of hysteresis. New core analysis and reservoir evaluation techniques are needed for shale. Abstract: Persistent uncertainties in understanding fluid phase behavior in natural nanoporous media, including shale rock, remain a significant challenge to fully utilizing tight geological formations as both globally significant sources of hydrocarbon fuels and repositories for greenhouse gas sequestration. By measuring isotherms of n-butane and n-pentane in kerogen-rich shale cores at temperatures from 4.9 to 65.6 °C, we show that shale nanopores can induce a phase transition known as capillary condensation upon adsorption or capillary evaporation upon desorption. For both adsorbates, capillary condensation and capillary evaporation took different paths, thus forming hysteresis loops that increased in size with increasing temperature. While isotherms of n-butane were expectedly reproducible, surprisingly those for n-pentane were not. This was due to irreversible kerogen swelling induced by the n-pentane. To further investigate this phenomenon, we measured scanning isotherms of n-pentane at 4.9 and 65.6 °C. Similar to the primary hysteresis loops, successive scanning measurements during adsorption resulted in different isotherm shapes, while those for desorption remained consistent. This implies differences in the physics governing adsorption and desorption, which may rely on the pore structure and fluid elasticity, respectively. These results comprise the first observations of hysteresis loop broadening at high temperatures, irreproducible hysteresis, and scanning isotherms during capillary condensation measurements in a natural nanoporous medium. By viewing these results in the context of the current hypotheses on capillary condensation derived from previous studies using synthetic nanopores, we conclude that new core analysis and reservoir modeling procedures must be developed to account for the irreproducible hysteresis at reservoir temperature.